Digitalization of Management and Correlation With The Quality of Student Administration Services - Mila Khairunnisa; Wahyu Hidayat; Neng Gustini (Journal of Educational Management Research, 2026)
This study examines the correlation between management digitalization and the quality of student administration services at Senior High Schools. Digital management involves leveraging technology to transform educational resources from analog to digital, including attendance, e-report cards, and learning platforms, and to enable AI for personalization, data storage, and IoT for facility monitoring. Student administration encompasses planning, student admissions, attendance, discipline, and the Student Council (OSIS). A quantitative, descriptive correlational approach was used with 261 eleventh-grade students selected using the Slovin formula. Data were obtained through a Likert-scale questionnaire and analyzed using instrument testing (validity and reliability), classical assumption tests (normality and linearity), and correlation/determination tests. The results indicate a high level of management digitalization (average 3.97) and high service quality (3.85). There was a strong and significant positive correlation (r = 0.806, p = 0.001 < 0.05), with digitalization explaining 65% of the variation in service quality (R² = 0.650). In conclusion, optimizing digitalization improves efficiency, transparency, and responsiveness, although improvements in response speed, assurance, and empathy are needed for staff. Findings were limited to this school.